Mata Magnet Ikan : Inovasi Teknologi Alat Pengumpul dan Pendeteksi Ikan Untuk Peningkatan Hasil Tangkapan Nelayan - Mutma'innah Hasan; Ahmad Satari Idris; M. Ikhwan Resya; M. Ikbal; M. Fadhel; M. Kurnia (Universitas Hasanuddin, 2021)
Fishing activities are exploration and exploitation activities of fishery resources. In addition to requiring knowledge about the resources to be caught, in terms of type, distribution and season, they also require information on effective and efficient fishing gear technology and fishing aids. The problem faced by the Jaring Rahmat fishing group in fishing operations is that it is difficult to collect and detect the presence of fish. Therefore, our team offers a solution, namely making a tool called fish magnet eye as an innovation in technology for collecting and detecting fish to increase fishermen's catches. With this tool, fishermen can produce larger catches because it will be easier to collect and detect the presence of fish so that fishermen's income will increase.